The moderating role of internet addiction severity on the relationship between affective temperaments and emotion regulation in adolescents and young adults - Mento, Carmela; Mollaioli, Daniele; La Barbiera, Chiara; Arena, Federica; Capellupo, Francesca; Muscatello, Maria Rosaria Anna; Lombardo, Clara (Frontiers in Psychology, 2025)
IntroductionAdolescence and young adulthood are critical periods for the development of emotion regulation, a process increasingly influenced by the pervasive use of digital technologies. This study investigated whether the severity of Internet Addiction (IA) moderates the relationship between affective temperaments and emotion regulation strategies in adolescents and young adults with problematic Internet use.MethodData were collected from a convenience sample of 262 Italian participants (62.6% female; aged 13–21) via an online survey between March and December 2024. Participants completed validated measures of Internet addiction (IAT), affective temperaments (TEMPS-A), and emotion regulation strategies (ERQ), and analyzed with different moderation models for each affective temperament.ResultsModeration analyses revealed that IA severity significantly weakened the negative association between depressive and anxious temperaments and cognitive reappraisal, and also reduced the positive link between anxious temperament and suppression, indicating that higher problematic Internet use may buffer some temperament-related emotion regulation difficulties.DiscussionFindings suggest that IA severity moderates the link between affective temperaments and emotion regulation. Specifically, higher IA levels weakened the negative association between depressive/anxious temperaments and cognitive reappraisal, and also reduced the positive link between anxious temperament and suppression, indicating that problematic Internet use may buffer some temperament-related emotion regulation difficulties. Future longitudinal research is needed to clarify the long-term impact of this digital scaffolding on emotional development.